Danny Lyon - Message to the future - Lyon, Danny 1942- (Yale University Press, 2016)
"Coming of age in the 1960s, the photographer Danny Lyon (b. 1942) distinguished himself with work that emphasized intimate social engagement. In 1962 Lyon traveled to the segregated South to photograph the civil rights movement. Subsequent projects on biker culture, the demolition and redevelopment of lower Manhattan, and the Texas prison system, and more recently on the Occupy movement and the vanishing culture in China's booming Shanxi Province, share Lyon's signature immersive approach and his commitment to social and political issues that concern those on the margins of society. Lyon's photography is paralleled by his work as a filmmaker and a writer. Danny Lyon: Message to the Future is the first in-depth examination of this leading figure in American photography and film, and the first publication to present his influential bodies of work in all media in their full context. Lead essayists Julian Cox and Elisabeth Sussman provide an account of Lyon's five-decade career. Alexander Nemerov writes about Lyon's work in Knoxville, Tennessee; Ed Halter assesses the artist's films; Danica Willard Sachs evaluates his photomontages; and Julian Cox interviews Alan Rinzler about his role in publishing Lyon's earliest works. With extensive back matter and illustrations, this publication will be the most comprehensive account of this influential artist's work"
"This catalogue is published by the Fine Arts Museums of San Francisco in association with Yale University Press on the occasion of the exhibition Danny Lyon: Message to the Future, Whitney Museum of American Art, New York, June 17-September 25, 2016, de Young, Fine Arts Museums of San Francisco, November 5, 2016-March 12, 2017, Fotomuseum Winterthur, May 20-August 27, 2017, C/O Berlin Foundation, September 15-December 10, 2017"--Colophon
Keywords: Lyon, Danny / Criticism and interpretation; Lyon, Danny -- 1942-; Geschichte 1962-2009; Gesellschaft; Documentary photography; Photography, Artistic; Photography / Social aspects; Dokumentarfotografie; Fotografie; Ausstellungskatalog -- Whitney Museum of American Art -- 17.06.2016-25.09.2016 -- New York, NY; Ausstellungskatalog -- De Young Museum -- 05.11.2016-12.03.2017 -- San Francisco, Calif.; Ausstellungskatalog -- Fotomuseum Winterthur -- 20.05.2017-27.08.2017 -- Winterthur; Ausstellungskatalog -- C/O Berlin Foundation -- 15.09.2017-10.12.2017 -- Berlin